The Philosophy of Science: Rationalism and Empiricism - Irgi I; Ramsiah Tasruddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the comparison between rationalism and empiricism from an epistemological perspective. These two schools of thought hold opposing principles regarding the sources, validity, and modes of reasoning in acquiring knowledge. The objectives of this study are to describe the background of the emergence of both schools, analyze the sources of knowledge, explain the criteria for truth validity, and describe the modes of reasoning of rationalism and empiricism. The method used is descriptive-analytical with a comparative approach and library research. The results show that rationalism emerged from the crisis of scholastic thought and the scientific revolution of the 17th century; its source of knowledge is reason (a priori knowledge), and truth validity is universal and certain through the deductive method. Empiricism emerged as a critique of rationalism; its source of knowledge is sensory experience (a posteriori knowledge), and truth validity is contingent and open to revision through the inductive method, which serves as the foundation of modern scientific methodology. In conclusion, although fundamentally opposed in principle, the two schools complement each other in contemporary scientific practice. An integrative understanding of rationalism and empiricism is crucial in the information age as a foundation for critical, systematic, and responsible thinking in education, research, and public policy.